A10.07 The kinetic cytokine/chemokine secretory profile in surgical models of osteoarthritis. (24th February 2016) - Ortiz, AC; Dunning, L; Huesa, C; Ferrell, WR; McInnes, IB; Lockhart, JC; Goodyear, CS; Crilly, A
Abstract : Background and objectives: Destabilisation of the medial meniscus (DMM) and section of the anterior cruciate ligament (ACL) are commonly used in vivo models of osteoarthritis (OA). Using explant culture, the secretory profile of synovium and patellar ligament was evaluated in DMM and ACL models. Material and methods: All murine procedures were Home Office (UK) approved. OA was induced in 10–12 week old C57BL/6 male mice by either DMM or ACL (1). SHAM and naïve animals were used as controls. Knee joint diameter (KJD) was assessed prior to induction of arthritis and every three days thereafter. At 4 and 12 weeks post-surgery, synovium and patellar ligament were harvested and used for explant culture. Supernatants were collected after 4 h and analysed by Luminex. In parallel experiments, joints were collected for histological analysis ofF4/80+, IL-33+ and CCR4+ cells in synovium and ligaments. Freund's complete adjuvant (FCA) monoarthritis model was used as a positive control of inflammatory joint disease. Data were expressed as mean values ±SEM (n = 6) and analysed using a 1 or 2 way ANOVA, with p < 0.05 as the criterion of significance. Results: At 4 weeks post-surgery no change in KJD was observed in either DMM or ACL. Nonetheless, secretion of MIP-1β/CCL4 was significantly increased in explant cultures from DMM and ACL compared to naïve controls (p < 0.001). In comparison, IL-33 was only significantly elevated in ACL cultures (p < 0.02). Histological evaluation of both OA models revealed the presence of F4/80 + macrophage, IL-33 and CCR4 (receptor for CCL4) in the synovium but not in the patella ligament. At 12 weeks post-surgery, IL-33 and IL-6 were the only cytokines detected in OA explant cultures, however, IL-33 levels were significantly reduced compared to 4 weeks post-surgery (p < 0.001). Conclusion: This study characterised the secretory profile of DMM and ACL joint tissue at 4 and 12 weeks post-surgery. This profile alters with time, with reduced IL-33 and an absence of CCL4 at 12 weeks. The potential role of IL-33 and CCL4 in the early and late stage pathogenesis of these OA models merits further investigation. Reference: Glasson SS, et al . The surgical destabilization of the medial meniscus (DMM) model of osteoarthritis in the 129/SvEv mouse. Osteoarthritis Cartilage. 2007;15(9):1061–1069